2015
DOI: 10.2174/1570162x13666150121105221
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Cycle and HIV-1 Tat Protein Influence Cocaine-Conditioned Place Preference and Induced Locomotion of Female Mice

Abstract: The HIV-1 trans-activator of transcription (Tat) protein, interacts with psychostimulants to potentiate cocaine-reward in rodents. Sex steroids may protect against Tat-induced deficits. Female GT-tg transgenic mice conditionally-expressed Tat protein targeted to brain via a doxycycline-dependent, GFAP-linked promoter. Mice were tested for cocaine-conditioned place preference (CPP) and cocaine-induced locomotion when in the proestrous (high-hormone) or diestrous (low-hormone) phases of their estrous cycle. Coca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…The concentration of Dox that was previously demonstrated to optimally express Tat protein in the GT-tg brain (100 mg/kg, i.p. [8,23]), concurrent with impaired learning [23], enhanced anxiety-like behavior [8,9], and potentiated drug reward [3133] was also the most efficacious concentration observed herein. Notably, effects on ASR and PPI were not linear; rather, acute Tat induction (after 1 day of Dox) or prolonged exposure (after 7 days of Dox) equally potentiated startle and impaired PPI.…”
Section: Discussionmentioning
confidence: 76%
“…The concentration of Dox that was previously demonstrated to optimally express Tat protein in the GT-tg brain (100 mg/kg, i.p. [8,23]), concurrent with impaired learning [23], enhanced anxiety-like behavior [8,9], and potentiated drug reward [3133] was also the most efficacious concentration observed herein. Notably, effects on ASR and PPI were not linear; rather, acute Tat induction (after 1 day of Dox) or prolonged exposure (after 7 days of Dox) equally potentiated startle and impaired PPI.…”
Section: Discussionmentioning
confidence: 76%
“…The optimized dose of Dox was chosen because it has been previously proven efficacious for induction of Tat (Zou et al, 2007;Carey et al, 2012;Paris et al, 2014b), and findings have shown that iTat so induced is biologically active during the period of behavioral testing (Zou et al, 2007). The 7-or 14-day Dox or saline treatment paradigm was chosen for the kinetic analysis of DA uptake based on the previous behavior studies (Carey et al, 2012(Carey et al, , 2013Paris et al, 2014a). In addition, based on the previous report that showed no significant difference in Tat immunoreactivity in whole brain of iTat-tg mice after 7 or 14 days' administration of Dox (Paris et al, 2014b), and because no difference in the inhibitory effects of Tat on DA uptake were observed between these time points, only the 7-day administration paradigm was used in the subsequent studies.…”
Section: Methodsmentioning
confidence: 99%
“…All mice (Tat− and Tat+) were administered 100 mg/kg Dox (doxycycline hyclate; Sigma-Aldrich, St. Louis, MO, USA) by intraperitoneal injection once a day for 7 days. This regimen was previously shown to induce Tat effectively [43][44][45] . Specifically, Tat expression increases during Dox administration and wanes significantly over 14 days after the termination of Dox treatment 45 .…”
Section: Doxycycline (Dox) Regimenmentioning
confidence: 99%